2014
DOI: 10.3109/0284186x.2014.923583
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk of rash to mTOR inhibitors in cancer patients – a meta-analysis of randomized controlled trials

Abstract: Background. Inhibitors of the mammalian target of rapamycin (mTOR) are currently approved for the treatment of several cancers, and their use is associated with serious rash, which affects patient ' s quality of life and leads to undesirable dose reductions or interruptions. A meta-analysis of randomized controlled trials (RCTs) was performed to determine the overall risk of developing high-grade rash with mTOR inhibitors in cancer patients. Methods. We searched the PubMed database and abstracts presented at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Points are given for studies that specify randomization, denote the specific method of randomization, mention double-blind trial design, explain appropriateness of double blinding, and describe the study's dropouts and withdrawals [14]. Our interpretation of study quality using the Jadad score is consistent with meta-analyses in the literature [15,16].…”
Section: Study Selectionsupporting
confidence: 52%
“…Points are given for studies that specify randomization, denote the specific method of randomization, mention double-blind trial design, explain appropriateness of double blinding, and describe the study's dropouts and withdrawals [14]. Our interpretation of study quality using the Jadad score is consistent with meta-analyses in the literature [15,16].…”
Section: Study Selectionsupporting
confidence: 52%
“…According to meta-analyses including patients with NETs, treatment with everolimus as well as other mTOR inhibitors, is most commonly associated with an increased risk of stomatitis [150153], rash[151,154], fatigue[155], infection[156], pulmonary toxicities [152,157,158], hyperglycemia[155,159], anemia[160,161], and thrombocytopenia[160]. The pharmacokinetic analysis of RADIANT-2 trial also revealed that an increased everolimus minimum concentration was associated with higher risk for pulmonary and metabolic events[64].…”
Section: Safety Of Everolimus (Table 6)mentioning
confidence: 99%